Perceived risk of security and privacy in online shopping: a study of Malaysia context - Jadehkenari, Marzieh Zendehdel; Paim, Laily (Marsland Press, 2012)
Online shopping is a new phenomenon in the field of E-Business and is certainly going to be the future of shopping in the world. Though online shopping is very common outside Malaysia, its growth in Malaysian Market, which is a large and strategic consumer market, is still not in line with the global market. The present research paper has used exploratory study to highlight the various factors and variables impacting the behavior of consumers towards on-line shopping in Malaysia. Data was collected from students’ samples in Malaysia. SEM (Structural Equation Model) was used to test the hypotheses and confirmed the fit of the model. The researcher found that there are three factors for explaining attitude and intention towards online shopping, which are privacy, security and subjective norm. The results show that if students worry about whether their information due to the process of online shopping will be used for other purposes, it will reduce their purchase attitude.